2000
DOI: 10.1002/1526-4998(200010)56:10<909::aid-ps227>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

[14C]Glyphosate transport in undisturbed topsoil columns

Abstract: Although glyphosate (N-(phosphonomethyl)glycine) is one of the most frequently used herbicides, few controlled transport experiments in undisturbed soils have been carried out to date. The aim of this work was to study the in¯uence of the sorption coef®cient, soil-glyphosate contact time, pH, phosphorus concentration and colloid-facilitated transport on the transport of [ 14 C]glyphosate in undisturbed top-soil columns (20 cm height  20 cm diameter) of a sandy loam soil and a sandy soil. Batch sorption experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 19 publications
1
18
0
3
Order By: Relevance
“…Several soil factors may have contributed to this diff erence with respect to signifi cance of particle-facilitated transport, for instance number of fl ow active continuous macropores, degree of preferential fl ow, the soil surface structure (see next paragraph), etc. For instance, the columns used in this setup were considerably larger (diameter 30 cm, length 50 cm) than columns used in experiments conducted by de Jonge et al (2000) (diameter 20 cm, length 20 cm). Th e larger column size reduces eff ects of lower boundary (saturation at 40-50 cm depth instead of at 15-20 cm depth) and takes better into account eff ects of structural heterogeneity in arable soils.…”
Section: Relative Signifi Cance Of Particle-facilitated Transportmentioning
confidence: 97%
See 1 more Smart Citation
“…Several soil factors may have contributed to this diff erence with respect to signifi cance of particle-facilitated transport, for instance number of fl ow active continuous macropores, degree of preferential fl ow, the soil surface structure (see next paragraph), etc. For instance, the columns used in this setup were considerably larger (diameter 30 cm, length 50 cm) than columns used in experiments conducted by de Jonge et al (2000) (diameter 20 cm, length 20 cm). Th e larger column size reduces eff ects of lower boundary (saturation at 40-50 cm depth instead of at 15-20 cm depth) and takes better into account eff ects of structural heterogeneity in arable soils.…”
Section: Relative Signifi Cance Of Particle-facilitated Transportmentioning
confidence: 97%
“…Except for Hardy et al (2000), who found that the pesticide difl ufenican was entirely associated with sediment in drain water, other reported quantifi cations of facilitated transport of strongly sorbing pesticides range from < 1 to 11% for leached glyphosate from columns (de Jonge et al, 2000), 13 to 16% and 16 to 31% of leached glyphosate and pendimethalin, respectively, in fi eld drain (Kjaer et al, 2007), to 4.9 to 30% for atrazine sampled in lysimeter (Sprague et al, 2000), and 6% of leached prochloraz sampled in drainage (Villholth et al, 2000). Th us, particle-facilitated transport accounting for 68% of the total leaching of glyphosate in conventionally tilled soil is a very high estimate compared to most other fi ndings.…”
Section: Relative Signifi Cance Of Particle-facilitated Transportmentioning
confidence: 99%
“…Particulate matter is efficiently filtered out in matrix flow, but significant particle-bound transport in macropores has been demonstrated for strongly sorbing solutes, including some pesticides (e.g. Worrall et al, 1999;Villholth et al, 2000;De Jonge et al, 2000;Zehe & Flu¨hler, 2001a;Petersen et al, 2002) and phosphorus (Ule´n & Persson, 1999;Stamm et al, 1998;Laubel et al, 1999;Uusitalo et al, 2001;De Jonge et al, 2004). An absence of significant sorption retardation during flow in larger macropores has also been indirectly demonstrated in several field experiments that show an equally fast initial breakthrough of solutes irrespective of their sorption characteristics (e.g.…”
Section: The Physics Of Water Flow and Solute Transport In Macroporesmentioning
confidence: 99%
“…'rainsplash') with the resident soil water in the distribution zone at or close to the soil surface. Conversely, leaching can be considerably reduced, either if dry weather follows application so that sufficient time is allowed for the solute to diffuse away from the soil surface, or if the solute is 'washed' into the soil matrix by one or more light rain showers which do not generate macropore flow (Isensee et al, 1990;Shipitalo et al, 1990;Edwards et al, 1993;De Jonge et al, 2000). Once the bulk of the chemical has penetrated into the soil matrix below the distribution zone, it is no longer so readily exposed to macropore flow (Gish et al, 1991a), since the micropore volume is much larger than the volume of macropores and very slow diffusion towards macropores becomes the rate-limiting factor.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…For instance, when the soil water content is high and heavy rainfall occurs shortly after application, macropore transport of glyphosate may take place (de Jonge et al 2000;Kjaer et al 2003). On the other hand, in a lysimeter study Fomsgaard et al (2003) found residues of glyphosate in subsoil and subsurface leachate water even two years after application, when heavy rainfall occurred after a long dry period.…”
mentioning
confidence: 99%